PENGARUH FASILITAS DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA SMP NEGERI 3 KECAMATAN XIII KOTO KAMPAR - Putri Nurarifa Santri; Suarman Suarman; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research goal is to know the influence of facilities and learning motivation toward students learning achievement in social science lesson. The population is at grade 8 students of SMPN 3 XIII Koto Kampar totally 59 students. All students are taken to be research sample. Data is collected trough documentation and questionnaire technigues. Data then is analysed used multiple regression analysis. The results of the study note that the learning facilities that are owned by students are mostly still inadequate. As for the motivation to learn it turns out most of the students have motivation with the category of being. Furthemore, from the results of data analysis, the results obtained that learning facilities have a positif and significant impact on learning achievement, the same thing there is also a positive and significant influence of learning motivation on learning achievement, and together it turns out learning facilities and learning motivation also has a positive and significant influence on learning achievement with a contribution of 31,7%. Thus, it can be said that to improve learning achievement in need of the availability of learning facilities are very adequate and supported by high learning motivation.Keywords: Learning Facilities, Learning Motivation, Learning Achievement.